Is moderation of protease production an adaptation of well-defined anthropization in dermatophytes? - Gokulshankar S; Ranjitsingh AJA; Venkatesan G; Ranjith M; Vijayalakshmi G; Prabhamanju M; Subashini S (Wolters Kluwer Medknow Publications, 2010)
The protease activity of different isolates of dermatophytes representing different ecological groups namely geophilic, zoopahilic and anthropophilic, in their vegetative and sporulation growth phases were compared. Unlike their geophilic and zoophilic counterparts, all the isolates of anthropophilic dermatophytes viz. Trichophyton rubrum, T. mentagrophytes, T. tonsurans, T. violaceum and Epidermophyton floccosum recorded reduced protease activity during artificially induced sporulation phase in comparison to their vegetative growth phase. Even among the anthropophilic group, a classical moderation of protease activity was recorded in Trichyphyton rubrum which also correlates to its clinical manifestation. This enzyme moderation could also be an evolutionary adaptation of the anthropization of these species